2013
DOI: 10.1371/journal.pone.0082689
|View full text |Cite
|
Sign up to set email alerts
|

Transmural Ultrasound Imaging of Thermal Lesion and Action Potential Changes in Perfused Canine Cardiac Wedge Preparations by High Intensity Focused Ultrasound Ablation

Abstract: Intra-procedural imaging is important for guiding cardiac arrhythmia ablation. It is difficult to obtain intra-procedural correlation of thermal lesion formation with action potential (AP) changes in the transmural plane during ablation. This study tested parametric ultrasound imaging for transmural imaging of lesion and AP changes in high intensity focused ultrasound (HIFU) ablation using coronary perfused canine ventricular wedge preparations (n = 13). The preparations were paced from epi/endocardial surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…For example, the APD 50 is longest at endocardium but shortest at epicardium. However, our previous work demonstrated that the changes of APD 50 across the depth direction of myocardium during HIFU ablation were similar (Wu et al 2013), suggesting the temperature-EP correlation derived from the surface measurement can still be applicable for subsurface condition. Nevertheless, the surface measurements in this study where the EP and temperatures were obtained from the same tissue layer can be correlated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the APD 50 is longest at endocardium but shortest at epicardium. However, our previous work demonstrated that the changes of APD 50 across the depth direction of myocardium during HIFU ablation were similar (Wu et al 2013), suggesting the temperature-EP correlation derived from the surface measurement can still be applicable for subsurface condition. Nevertheless, the surface measurements in this study where the EP and temperatures were obtained from the same tissue layer can be correlated.…”
Section: Discussionmentioning
confidence: 98%
“…For the first time, the thermal dose threshold (log 10 ( CEM 43 )) for causing significant APA changes was calculated to be greater than −5.30 ± 0.13. Since APA changes are predominantly affected by the kinetics of sodium ion channels, the slight APA reduction at the early stage is likely due to the changes in diffusion rate of sodium upon HIFU induced temperature increases, whereas multiple effects including rises of RMP, blocking of fast sodium channels (Wu et al 2013), and structural changes of cellular membrane (Jin et al 2006) were potentially involved when temperature was further increased by HIFU and drastic APA reduction occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the abundant blood ow in the myocardium seriously affects the ablation effect of HIFU. Previous studies have found that under the conditions of the same HIFU intensity and irradiation time, the heat generated in the blood-rich tissues would be quickly removed by the blood ow, and the extent of tissue necrosis would be affected [27] . An abundant vascular bed can not only reduce the peak temperature rise caused by HIFU, but also reduce the size and change the shape of the injury.…”
Section: Discussionmentioning
confidence: 99%
“…The next step is real time assessment of lesion creation which can be potentially provided by methods to measure tissue temperature and assess necrosis. 2931 High resolution recording methods also have the potential to better define effective ablation lesions. While radiofrequency current will remain a simple, safe and easily applied energy source for ablation, a number of other energy sources for ablation will find applications for difficult arrhythmia substrates.…”
Section: Diagnostic Strategiesmentioning
confidence: 99%
“…The inadequate lesion depth for some intramural substrates will be addressed with bipolar ablation from electrodes bracketing the target area, intramural needle ablation, and alternative energy sources, such as microwave and ultrasound energy, which do not require tissue contact to produce deep tissue heating. 3134 …”
Section: Diagnostic Strategiesmentioning
confidence: 99%